Peran Legio Maria Dalam Mengembangkan Spiritual Dan Karakter Baik Mahasiswa Perantauan Presidium Maria Tak Bernoda Janti - Fransiska Adel Lewar; Intansakti Pius X (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this article is to explain how the Legion of Mary prayer community is a suitable place for overseas students to develop their spirituality and good character. By becoming a member of the Legion of Mary one can develop their faith and can achieve higher glory in Spiritual matters. This research uses the method of literature study and interviews with all Legionary members of the presidium of Mary Immaculate Janti. From the results of the interviews it can be said that the Legion of Mary has a positive impact on them both physically and spiritually.